Cutting parameters optimization of Al-6063 using numerical simulations and genetic algorithms (2019)
Machining process simulations are commonly used by manufacturing industries to accurately predict machining force, time, and the performance of engineering components. Determination of optimal conditions of machining parameters is fundamental to improve material properties, surface finish quality, and the cutting tool life, among other objectives. There are two alternatives to determine optimal cutting parameters for a given process. The first one is through the use of machining handbooks, which often offers different alternatives based on experience, hence generating uncertainties and drawbacks in terms of efficiency of the solution. The second alternative to the conventional method is the development of complex computational models, which makes process optimization problem more difficult and sometimes impossible to solve. In this work, a multi-objective genetic algorithm based on orthogonal cutting finite element (FE) simulations and statistical analysis is proposed to determine optimal machining parameters, being rake angle ({alfa}), velocity V and cutting feed (f). The optimal conditions are achieved by minimizing the cutting force, grain size ({delta}), and maximizing material removal rate (MRR) of Aluminum 6063-O. Response surface methodology (RSM) has utilized for the optimization process to examine the influence of the process parameters in cutting process performance. FE simulations are carried out using MSC Marc by taking into account a Johnson-Cook constitutive model for material plastic behavior and an entropy-based damage model. Material response was determined by using three different test apparatus, a conventional quasi-static test apparatus, a drop weight impact test (DWIT), and a Klosky-Hopkinson bar machine, covering strain rate values from 0.01 s^(-1) to 30 s^(-1) and temperature values from 23°C to 300°C. Constitutive model, damage model, and computational domains were validated using tension tests, Taylor test, and experimental measurements of orthogonal cutting forces.